1998
DOI: 10.2337/diacare.21.6.949
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Genes for NIDDM: Design of the Finland—United States Investigation of NIDDM Genetics (FUSION) Study

Abstract: Our work demonstrates the feasibility of collecting a large number of affected sib-pair families with NIDDM to provide data that will enable a whole genome search approach, including linkage analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 13 publications
2
104
0
Order By: Relevance
“…The ongoing search for genes for Type II diabetes will provide new information about the genetic markers of interest. We will be able to determine whether those subjects with IGT who progress to Type II diabetes share certain susceptibility genes and whether subjects with certain genotypes respond particularly well to intensive lifestyle interventions based on the results of genetic studies currently going on in Finland [31].…”
Section: Methodsmentioning
confidence: 99%
“…The ongoing search for genes for Type II diabetes will provide new information about the genetic markers of interest. We will be able to determine whether those subjects with IGT who progress to Type II diabetes share certain susceptibility genes and whether subjects with certain genotypes respond particularly well to intensive lifestyle interventions based on the results of genetic studies currently going on in Finland [31].…”
Section: Methodsmentioning
confidence: 99%
“…The Finland-US Investigation of NID-DM (Type II diabetes mellitus) Genetics (FUSION) Study is an international collaborative effort with the goal of mapping and cloning the genes predisposing to Type II diabetes and intermediate quantitative traits in Finnish subjects [15]. The age at diagnosis of Type II diabetes in index cases from which the families were ascertained ranged from 35±60 years.…”
Section: Methodsmentioning
confidence: 99%
“…The FUSION study design, recruitment, and phenotyping have been detailed elsewhere (Valle et al 1998), and details regarding genotyping can be found in the companion article by Ghosh et al (2000 [in this issue]). Therefore, in this article we only briefly review recruitment and phenotyping.…”
Section: Subjects and Phenotypingmentioning
confidence: 99%
“…Fasting glucose, insulin, lipids, and resting blood pressure were measured in all study subjects. Fasting C-peptide and glutamic acid decarboxylase antibody (GAD Ab) were measured in diabetic individuals, and these values were used in conjunction with insulin-treatment information to identify possible cases of late-onset type 1 diabetes, as described elsewhere (Valle et al 1998). An oral glucose-tolerance test (OGTT), conforming to World Health Organization (1985) standards, was performed both in all nondiabetic subjects, to determine their glucose-tolerance status, and in diabetic subjects whose affection status could not be readily confirmed, yielding 2-h glucose and insulin measurements in these individuals.…”
Section: Subjects and Phenotypingmentioning
confidence: 99%